PREDICTING BANKRUPTCY OF SELECTED MANUFACTURING COMPANIES LISTED IN COLOMBO STOCK EXCHANGE: APPLYING ALTMAN’S Z-SCORE - S, Anandasayanan; V.A, Subramaniam (International Journal of Research -GRANTHAALAYAH, 2017)
Bankruptcy is the legal status for an individual or company incapable to pay off outstanding debt. Predication of Bankruptcy is critical task. Early stage of identification of likelihood of solvency may avoid evils in the near future & may shelter the firm from Bankruptcy situation. Bankruptcy of organizations can be predicated by using Altman’s Z-Score Model. This study tries to apply the model to understand the likelihood of Bankruptcy of selected listed manufacturing firms for past 5 years from 2010 to 2014 which are listed in Colombo Stock Exchange. The study reveals that four companies completely belong to Safe Zone for the entire period of study. Three firms are in Distress Zone which clearly indicates that these firms may go Bankrupt in near future.